Pengaruh Bagi Hasil, Disposable Income, Promosi Dan Pengetahuan Terhadap Minat Masyarakat Menabung Di Bank Syariah (Studi Kasus Masyarakat Kecamatan Cilongok) - Elsa Nurardiva Windatania; Siti Ma’sumah; Riztina Dwi Setyasih; Dwi Ayu Setyoningrum (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aimed to determine the influence of profit sharing, disposable income, promotion, and knowledge on savings interest in Islamic banks among residents of Cilongok District. This study employed quantitative research methods. Data were collected through a questionnaire involving 100 residents of Cilongok District as the population and sample. The results indicate that profit sharing and knowledge significantly influence the interest of residents of Cilongok District to save in Islamic banks, while disposable income and promotion did not show significant results. Simultaneously, profit sharing, disposable income, promotion, and knowledge significantly influence the interest of residents of Cilongok District to save in Islamic banks.